Nationhood as ethical orientation among Polish Catholic migrants in Denmark. - Petersen, Michael Brixtofte (Journal of Ethnic & Migration Studies, 2025)
This article presents an ethnographic study of diasporic nationhood, Catholicism, and ethical navigation among Polish migrants in Denmark. Focusing on a vibrant Polish Catholic community in Copenhagen, the study utilises fieldwork and 25 semi-structured interviews gathered from 2021 to 2023 to explore the under-researched role of a nationalised Catholicism as a repertoire of guidance in a migratory setting. The conceptual framework combines a praxiological approach to diasporic nationhood with the notion of ethical affordances. Foregrounding specific modalities of connections between Catholic Polish nationhood and ethical guidance, the study expands the perspectives on how migrants actively engage Catholicism amid their lives of transition and accommodation in Denmark. Based on such focus, the analysis shows how this connection enables both an ethical navigation in new terrain, but also an opposition to the secular public outside the church environments. Within the nascent social scientific study of Catholicism and migration, the study contributes by analytically combining these elements – diasporic nationhood and ethical navigation – thereby providing novel insights into the often overlooked ethical and religious experiences of post-accession Polish migrants, and the ethical difference a nationalised form of Catholicism makes.